(untitled) (Applied Biological Research, 2020)
Beetroot is recognized as health promoting food due to presence of essential components such as vitamins, minerals, phenolics, carotenoids, nitrate, ascorbic acids and betalains that promote health. Good quality beetroot samples (100) were randomly taken and characterized for physical properties viz., shape, length, width and thickness. Derived dimensional properties like geometric diameter, equivalent diameter, arithmetic diameter, sphericity, surface area, aspect ratio, bulk density, true density, peel thickness, angle of repose and packing coefficient were alculated. These properties are necessary for designing the equipment for harvesting, sorting, separating and packing. The mean values of sphericity and surface area were found to be 0.91 and 79.63 cm2. The average values of aspect ratio, peel thickness and angle of repose were 0.94, 1.06 mm and 40.67°, respectively. The drying experiments were carried out under three air temperatures of 40, 50 and 60°C, air velocity of 1.0 m/s beetroot slice thickness of 2 mm. The colour parameters for colour change of the materials were quantified by Hunter (Lab) system. These values were also used to calculate the total colour change, chroma, Hue angle and browning index. It was observed that L, a, b and chroma were fitted to first order kinetics model, whereas ∆E and Hue angle followed zero order kinetic model.